Sensitive Zn2+ sensor based on biofunctionalized nanopores via combination of DNAzyme and DNA supersandwich structures. Issue 12 (25th February 2016) - Liu, Nannan; Hou, Ruizuo; Gao, Pengcheng; Lou, Xiaoding; Xia, Fan
Abstract : Isothermal amplification of Zn 2+ detection is achieved by using a DNA supersandwich structure and Zn 2+ -requiring DNAzymes in nanopores. Abstract : The sensitivity of detection based on biofunctionalized nanopores is limited since the target-to-signal ratio is 1 : 1. Isothermal amplification is a promising amplification strategy at constant temperature due to its easy operation, quick results, PCR-like sensitivity, low cost and energy efficiency. In the present work, the isothermally amplified detection of Zn 2+ is achieved by using a DNA supersandwich structure and Zn 2+ -requiring DNAzymes. The DNA supersandwich structures, due to the multiple amplification of nucleic acids, heavily plug the nanopore. Simultaneously, the DNA supersandwich structures bond with the sessile probe (SP) of the substrate in the nanopore which partially hybridizes with DNAzymes. In the presence of Zn 2+, the Zn 2+ -requiring DNAzyme cleaves the SP into two fragments, while the DNA supersandwich structures are peeled off and the ionic pathway is unimpeded. A steep drop and a sequential complete recovery of the current occur in the I – V plot when the DNA supersandwich structures are decorated and peeled off. In the present system, the reliable detection limit of Zn 2+ is as low as 1 nM. Discrimination between different types of ions (Cu 2+, Hg 2+, Pb 2+ ) is achieved.